IMPLEMENTATION OF STRATEGIC MANAGEMENT IN IMPROVING APPARATUS PERFORMANCE AT THE NORTH MANDREHE DISTRICT OFFICE - Novamataroeli Lahagu; Meiman Hidayat Waruwu; Sukaaro Waruwu; Palindungan Lahagu (LPPM YPITI, 2026)
This study aims to analyze the Implementation of Management Strategies in Improving Apparatus Performance at the North Mandrehe Sub-district Office, identify the obstacles faced, and assess the impact of the implementation of these strategies on apparatus performance and the quality of public services. The background of this study is based on the demand for improving the performance of local government apparatus in order to provide effective, efficient, and satisfying services to the public. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. Research informants consisted of the North Mandrehe Sub-district Head, Sub-district Secretary, Head of General Sub-division, employees, village heads, and community representatives. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of management strategies at the North Mandrehe Sub-district Office was carried out through participatory work planning, division of tasks according to job descriptions, application of SOPs, regular coordination and evaluation meetings, direct supervision, and periodic training. The obstacles faced include limited human resources and infrastructure, uneven motivation and discipline of apparatus, budget limitations, and suboptimal coordination between work units. The impact of implementing management strategies can be seen from the increased speed and efficiency of services, administrative productivity, discipline of the apparatus, positive employee responses, and public satisfaction, although its sustainability requires adequate resource support.